A Different Kind of War : The United States Army in Operation Enduring Freedom October 2001-September 2005 - Wright, Donald P. (Fort Leavenworth Combat Studies Institute Press, 2010)
A different kind of war' offers the first preliminary comprehensive historical account of OEF, tracing the development of the Afghanistan campaign from its inception in the fall of 2001 through the Afghanistan parliamentary elections of September 2005. To do so, the study takes a chronological approach to the story of the Army in Afghanistan in this period
Include Illustrations, Bibliography and Index
Keywords: Postwar reconstruction -- Afghanistan -- United States